Effects of green tea on glycemic status in female metabolic syndrome patients - Tabassum, Sabira; Akhter, Qazi Shamima (Journal of Bangladesh Society of Physiologist, 2020)
Background: According to International Diabetic Federation, around 20-25% of world adult population have the clinical features of metabolic syndrome (MetS). Different organizations recommend to modify lifestyle and dietary habit as primary intervention. Green tea has several pharmacological effects on metabolic diseases including MetS. Objective: To evaluate the effects of green tea consumption on two glycemic variables in women with MetS. Method: This interventional study was conducted in the Department of Physiology, Dhaka Medical College from January 2016 to December 2016. After fulfilling the ethical aspect, a total number of 42 female patients with MetS aged 40 to 50 years were selected from the outpatient department of Endocrinology, Dhaka Medical College Hospital. Participants were randomly assigned in study group (n=22) and control group (n=20). Study group consumed green tea for 12 weeks and the control group did not consume green tea. In both groups fasting serum glucose (FSG) and glycosylated hemoglobin (HbA1c) were measured by glucose oxidase (GOD/ PAP) method and modified high performance liquid chromatography (HPLC) method respectively 2 times (before and after 12 weeks). Data were analyzed by paired Student’s ‘t’ test and unpaired Student’s ‘t’ test. Results: After 12 weeks of intervention, FSG & HbA1c significantly (p<0.001) decreased in the study group than those of their baseline value and these values were also significantly (p<0.05) lower in comparison to those of control group. Conclusions: Regular consumption of green tea may improve glycemic status in patients with metabolic syndrome. J Bangladesh Soc Physiol. 2020, December; 15(2): 85-90